Cyprinid herpesvirus‐2 (CyHV‐2): a comprehensive review. (14th September 2020) - Thangaraj, Raja Swaminathan; Nithianantham, Sundar Raj; Dharmaratnam, Arathi; Kumar, Raj; Pradhan, Pravata Kumar; Thangalazhy Gopakumar, Sumithra; Sood, Neeraj
Abstract: Cyprinid herpesvirus‐2 (CyHV‐2) is a linear double‐stranded DNA virus in the genus Cyprinivirus of family Alloherpesviridae . The virus is known to be highly pathogenic to ornamental goldfish ( Carassius auratus ), crucian carp ( C. carassius ) and Gibel carp ( C. auratus gibelio ), and also to the hybrids of goldfish and other carps. Cyprinid herpesvirus‐2, having the smallest genome (290.3 kb) among Cyprinivirus, causes herpesviral hematopoietic necrosis disease (HVHND) that results in huge economic losses in aquaculture industry as the disease can cause high mortality (50–100%) among the affected fish. The disease was initially reported as the cause of epizootics in juvenile goldfish of Japan during 1992 and 1993. To date, this disease has been reported around the world including Europe, North America, Oceania and Asia. Huge economic losses due to the CyHV‐2 infection among cultured gibel carp in China, during 2011–2012, mass mortality in crucian carp during 2012 in Italy, 95% mortality in goldfish during 2014 in France, 85% mortality in goldfish during 2016 in Poland had been reported. Strategies for controlling the spread of CyHV‐2 are thus urgently required to limit economic damage. Furthermore, the review will shed light on lacunae in current knowledge as well as on the perspectives that merits further investigations on CyHV‐2 research. The paper forms the first comprehensive overview of CyHV‐2 causing a serious economically significant fish disease and, will be helpful for the researchers to get all related information from a single manuscript.